The Strategic Role of Management Accounting in Improving MSME Sustainability through Cost Control, Capital Structure, and HR Management in the Digital Era - Ahmad Gustomi; Ramadhani, Albareta Arum; Firantika, Diah Ayu; Anggraini, Firly; Faiqoh, Dina Nadiyah (PT FORMOSA CENDEKIA GLOBAL, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in national economic growth through job creation and GDP contribution. However, in today’s digital disruption era, they face challenges in operational efficiency, limited financing, and weak human resource management. This study explores the strategic role of management accounting in supporting MSME sustainability, focusing on cost control, capital structure, and HR development. Using a systematic literature review (SLR) of international journals and academic sources from the past decade, the study finds that digital-based management accounting such as big data, digital accounting systems, and activity-based costingimproves cost efficiency, decision-making quality, and HR capabilities. The research concludes that digital transformation in management accounting is a strategic necessity for MSME resilience and long-term sustainability.